323 ENGOT-en9/LEAP-001: a phase 3 study of first-line pembrolizumab plus lenvatinib compared with chemotherapy in advanced or recurrent endometrial cancer. (13th November 2020) - Randall, L; Marth, C; Vulsteke, C; Jesús Rubio, M; Makker, V; Braicu, I; McNeish, I; Madry, R; Ayhan, A; Hasegawa, K; Wu, X; Dutta, L; et al.
Abstract : Background: Prognosis and OS are poor in patients with advanced or recurrent endometrial cancer (EC). First-line standard of care for these patients is paclitaxel-carboplatin chemotherapy; however, more effective and tolerable therapies are needed. In the phase 1b/2 trial KEYNOTE-146, which assessed the PD-1 inhibitor pembrolizumab combined with the multikinase inhibitor lenvatinib, an ORR of 38% was observed in patients with previously treated advanced EC. ENGOT-en9/LEAP-001 (NCT03884101 ) is a randomized, open-label, active-controlled, phase 3 study investigating pembrolizumab + lenvatinib vs chemotherapy in patients with EC. Trial design: Patients with newly diagnosed advanced (stage III-IV) or recurrent EC not previously treated with antiangiogenic agents; systemic chemotherapy (unless within a chemoradiation regimen); PD-1, PD-L1, or PD-L2 inhibitors; or other T-cell receptor–targeted therapies will be eligible. Patients will be randomized 1:1 to receive pembrolizumab 200 mg Q3W + lenvatinib 20 mg daily or paclitaxel 175 mg/m2 Q3W + carboplatin AUC 6 Q3W. Randomization will be stratified by proficient vs deficient mismatch repair (pMMR vs dMMR) status. The pMMR population will be further stratified by prior chemoradiation (yes/no), measurable disease (yes/no), and ECOG performance status (0/1). Patients will receive treatment for ≤35 cycles of pembrolizumab vs 7 cycles of chemotherapy or until initiation of a new anticancer treatment, unacceptable AEs, or withdrawal of consent. Primary endpoints are PFS (per RECIST v1.1 by blinded independent central review) and OS. Secondary endpoints are ORR, health-related QOL, safety/tolerability, and lenvatinib pharmacokinetics. Exploratory endpoints are disease control rate, clinical benefit rate, and duration of response. Enrollment is ongoing.